P-238 Treatment options to overcome impaired fertilization and embryonic development caused by an oocyte-related deficiency in the Patl2-/- mouse model. (30th June 2022) - Cardona Barberán, A; Christodoulaki, A; Goethals, J; Thys, V; Vanden Meerschaut, F; Arnoult, C; Stoop, D; Boel, A; Heindryckx, B
Abstract: Study question: Can assisted oocyte activation (AOA) or spindle transfer (ST) overcome the lower fertilization and blastocyst rates observed in the Patl2 -/- mouse model? Summary answer: ST, but not AOA, has the potential to restore both normal fertilization and blastocyst rates in a mouse model with an oocyte-related deficiency. What is known already: PATL2 is an RNA-transcriptional repressor involved in the regulation of maternal mRNAs during oocyte maturation. Mutations in PATL2 have been detected in patients with oocyte maturation arrest, reduced fertilization and embryo developmental arrest. Consequently, these patients are mostly referred to oocyte donation. Both AOA, inducing artificially calcium oscillations by calcium ionophores, and ST, replacing bad-quality oocyte cytoplasm with healthy cytoplasm, have been proposed to treat oocyte-related infertility. However, there is a lack of studies showing which oocyte-related infertility indications may benefit from which specific treatment. The Patl2 -/- mouse model offers a unique opportunity to study the efficiency of these treatments. Study design, size, duration: An experimental study using C57BL/6NTac-Patl2tm1a mice was conducted between April to December 2021. Breeding of heterozygous C57BL/6NTac-Patl2tm1a mice resulted in a total of 156 pups, from which 22 were homozygous C57BL/6NTac-Patl2tm1a ( Patl2 -/- ) females. Metaphase II (MII) oocytes were collected from Patl2 -/- (test group) and Patl2 +/+ (control group) females and used to evaluate different oocyte quality markers, as well as the efficiency of AOA and ST treatments to improve the oocyte-related subfertility observed in Patl2 -/- mice. Participants/materials, setting, methods: Four- to 12-week-old mice were subjected to ovarian hyperstimulation and oocyte collection, where oocyte maturation was assessed. Afterwards, MII oocytes were used to evaluate oocyte diameter, spindle abnormalities, activation rate (AR) and blastocyst rate (BR) after PIEZO-ICSI and calcium releasing capacity after SrCl2 exposure. Finally, Patl2 -/- MII oocytes were treated with AOA, by direct exposure to SrCl2, or ST treatment, by transferring the Patl2 -/- spindle to Patl2 +/+ cytoplasm (previously enucleated) followed by SrCl2 exposure. Main results and the role of chance: No difference in the number of cumulus-oocyte complexes (COCs) and mature MII oocytes was observed between 6 Patl2 -/- mice (128 MII/159 COCs) and 5 Patl2 +/+ mice (108 MII/132 COCs). However, Patl2 -/- MII oocytes showed a significantly lower cytoplasm diameter (68, 11 ± 2, 25, n = 79) than Patl2 +/+ oocytes (75, 19 ± 2, 09, n = 77, p-value<0, 001), suggesting that Patl2 affects oocyte growth but does not seem to affect oocyte maturation. Nuclear maturity was not compromised either, as a similar percentage of oocytes with normal spindle was observed in Patl2 -/- (48, 4%, 15/31) and Patl2 +/+ MII oocytes (50%, 18/36). Activation and blastocyst rates after PIEZO-ICSI were lower in Patl2 -/- (AR = 45, 5%, 5/11 and BR = 20, 0%, 1/5) than in Patl2 +/+ (AR = 75, 0%, 21/28 and BR = 52, 4%, 11/21). In addition, total calcium released during oocyte activation after SrCl2 exposure was not different between Patl2 -/- (AxF=6, 88 AU, n = 30) and Patl2 +/+ MII oocytes (AxF=5, 04 AU, n = 28, p-value=0, 087). In line with these results, AOA treatment did not improve activation and blastocyst rates in Patl2 -/- oocytes (AR = 66, 7%, 44/66 and BR = 45, 5%, 20/44) compared to Patl2 +/+ oocytes (AR = 96, 5%, 110/114 and BR = 79, 1%, 87/110, p-value<0, 001). Nonetheless, when performing ST using Patl2 -/- as spindle donors and Patl2 +/+ as cytoplasm recipients, activation (8/8, 100, 0%) and blastocyst rate (6/8, 75, 0%) were restored to normal values. Limitations, reasons for caution: This study describes preliminary results and is limited by its small sample size. In addition, we did not identify an increased number of immature oocytes and spindle abnormalities in Patl2 -/- female mice in contrast to previously published reports. Wider implications of the findings: ST could be offered to treat PATL2- related female-infertility caused by a cytoplasmic deficiency, to increase both fertilization and blastocyst rates. AOA would not be beneficial for these patients as calcium releasing capacity of Patl2 -/- oocytes does not seem to be affected, suggesting a deficiency independent from calcium releasing machinery. Trial registration number: Not applicable